2020
DOI: 10.1101/2020.10.16.20214049
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Quantifying Asymptomatic Infection and Transmission of COVID-19 in New York City using Observed Cases, Serology and Testing Capacity

Abstract: The contributions of asymptomatic infections to herd immunity and community transmission are key to the resurgence and control of COVID-19, but are difficult to estimate using current models that ignore changes in testing capacity. Using a model that incorporates daily testing information fit to the case and serology data from New York City, we show that the proportion of symptomatic cases is low, ranging from 13% to 18%, and that the reproductive number may be larger than often assumed. Asymptomatic infection… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
23
0
2

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 60 publications
6
23
0
2
Order By: Relevance
“…4 displaying the time evolution of the R eff in the five French regions considered and in Ireland. Our estimates of the initial value of R eff lie in the range [3.,3.5] in agreement with other estimates [11,30].…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…4 displaying the time evolution of the R eff in the five French regions considered and in Ireland. Our estimates of the initial value of R eff lie in the range [3.,3.5] in agreement with other estimates [11,30].…”
Section: Resultssupporting
confidence: 91%
“…These biases are mainly due to the uncertainty in incidence data that can arise due to both the transmission characteristics of this virus (asymptomatic and pre-symptomatic transmission) and the quality and preparedness of the public health system. For COVID-19, it has been shown that the number of observed confirmed cases significantly underestimates the actual number of infections [10][11]. For instance, during the initial rapid growth phase of the COVID-19 epidemic, the number of confirmed case underestimated the actual number of infections by 50 to 100 times [10].…”
Section: Introductionmentioning
confidence: 99%
“…We explore by simulation how the optimal strategy for allocating a single type of test varies by 1) the number of available tests; and 2) the marginal probability of being asymptomatic for a truly infected individual,t a , in a hypothetical region of population 8 million. Although the true proportion of asymptomatic infections cannot be known without extensive testing and confirmation, existing literature suggests this proportion varies across regions, with estimates from around 30% to almost 90% [11,12,13].…”
Section: Resultsmentioning
confidence: 99%
“…The current evidence is not yet sufficient to support a conclusive value for this parameter. For the simulations presented here, we set a=0.85, based on a recent serological study conducted in New York City (NYC) that found anti-SARS-CoV-2 IGGs among 21.2% of the population [20]. This serological result, combined with simulation work, suggests that nearly 85% of exposed New Yorkers were asymptomatic or exhibited minor symptoms.…”
Section: Methodsmentioning
confidence: 99%